INSTITUTIONALIZING ILL-HEALTH: CORRUPTION AND HEALTH CARE IN INDIA - Karuvelil, John (Asian Horizons, 2012)
India is credited to have some of the most ancient and most effective systems of medicine like Ayurveda, Unani and Siddha. The assumption that Indians in general enjoyed better health is supported by the fact that even when the rest of the world suffered from deadly plagues and other fatal diseases during the middle ages and before India was spared from them. However, the fact that the country has not been able to maintain such good standards is again illustrated by the emergence of deadly diseases, including plagues, dengue, chikungunya, and so on, that are eradicated in most other parts of the world, especially the developed nations.